An Introduction to Software Tools, Data, and Services for Geospatial Analysis of Stroke Services - Padgham, Mark; Boeing, Geoff; Cooley, David; Tierney, Nicholas; Sumner, Michael; Phan, Thanh G.; Beare, Richard (Frontiers in Neurology, 2019)
Background: There are interests in the use geospatial data for development of acute stroke services given the importance of timely acess to acute reperfusion therapy. This paper aims to introduce clinicians and citizen scientists to the possibilities offered by open source softwares (R and Python) for analyzing geospatial data. It is hope that this introduction would stimulate interest in the field as well as generate ideas for improving stroke services. Method: Instructions on installation of libraries for R and Python, source codes and links to census data are provided in a notebook format to enhance experience with running these softwares. These codes illustrate different aspects of using geospatial analysis: 1)- creation of choropleth (thematic) map which depicts estimate of stroke cases per post codes; 2) use of map to help define service regions for rehabilitation after stroke. Results: Choropleth map showing estimate of stroke per post codes and service boundary map for rehabilitation after stroke. Conclusions The examples in this article illustrate the use of a range of components that underpin geospatial analysis. By providing an accessible introduction to these areas, clinicians and researchers can create code to answer clinically relevant questions on topics such as service delivery and service demand.